Nurse turnover and perceived causes and consequences: a preliminary study at private hospitals in Indonesia - Aryo Dewanto; Viera Wardhani (BMC, 2018)
Abstract Background Despite the inevitable growing rate of nurse turnover worldwide and its consequences, limited empirical data has been published in Indonesia. This study aims to describe the nurse turnover pattern at private hospitals, its causes and consequences as perceived by the hospitals' managers. Methods A survey method was used to obtain secondary and primary data from five private general hospitals in three administrative regions in East Java, Indonesia. The data of nurse turnover and demographic characteristics were collected. Mann Whitney test and relative risk analysis was performed to explore the role of nurse characteristics on nurses' decision to leave their job. To explore the causes and consequences of nurse turnover, an online survey was conducted to twelve hospital managers. The data was then classified based on similar themes. Results The data show that nurse turnover is between 12 and 34%. Being up to thirty years old, single, and having worked in the hospital up to three years significantly increase the risk of turnover. Personal reasons, external attractions and unsuitable working conditions are the three common nurse turnover reasons revealed by hospital managers. Hospital managers admitted that nurse turnover disturbs hospital operations, further impacting the hospital's revenue and costs. Conclusions The nurse turnover is higher than the acceptable level which is significantly predicted by age, marital status and job tenure. Further research is needed to develop nurse retention strategy in their early years of employment, based on the nurse's point of view.